Principles of Institutional-Evolutionary Political Economy -- Converging Themes from the Schools of Heterodoxy - O'Hara, Phillip Anthony (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
The article examines the renewed interest in heterodox political economy. Institutionalists, post Keynesians, neo-Marxists, and feminists among others, and various sub-groups provide schools of thought on heterodoxy. The guidelines of institutional-evolutionary political economy (IEPE) are offered alongside socioeconomic analysis and complexity theories. The author outlines the conflict of individual v. structure. Other topics covered include social capital, heterogeneous agents, financial instability, cumulative causation, institutional environments, community and governance, and destructive creation.
Keywords: Keynesian economics; creative destruction; disembedded economy; economic policy; evolutionary economics; heterodox economics; heterodox political economy; infrastructure (economics); mixed ability grouping (education); political economic analysis; social capital; social theory

Economic Surplus, Social Reproduction, Nurturance and Love - O'Hara, Phillip Anthony (Forum for Social Economics, 2011)
This paper examines the contributions of James Ronald Stanfield to social and political economy. We start the analysis with Stanfield's contribution to institution building through his education of PhD students, building a graduate program in political economy, and through the associations of social and political economy. Then we go on to scrutinise his creative developments and applications of the notions of economic surplus and social reproduction. This is followed by his extensive work on Karl Polanyi and the disembedded economy. Finally we explore his path-breaking analysis of the great capitalist restoration, the nurturance gap and love. Stanfield was one of the greatest institutionalists and social economists of the last hundred years, and these four areas of energetic creativity are his prime achievements in the area.
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; history of economic thought: individuals